Analysis of Corporate Governance, Intellectual Capital, and Financial Performance Using Conventional Methods and Maqashid Sharia Index (MSI) on the Implementation of Sustainable Finance in Sharia Banking in Indonesia - Praptiningsih, Praptiningsih; Nastiti, Heni; Nopiyanti, Anita (Dinasti International Journal of Economics, Finance & Accounting, 2022)
The banking industry certainly has a role to play in the success of this initiative through a sustainable finance program. Sustainable finance is a global trend that represents a new paradigm in the world of banking and other financial institutions that help implement sustainable development. Sustainable development is a development effort based on three directions: benefits, society, and protection of natural resources and the environment. In this study, the authors use traditional methods and the Makassid Shariah Index (MSI) to assess the impact of corporate governance, intellectual capital, and financial performance on sustainable financial practices in the Indonesian Islamic financial services industry. 2017-2021 (5 years). The sample of this research is processed from the annual report data of Islamic banks in Indonesia by using the panel data regression analysis method. Based on this research, the influence of corporate governance, intellectual capital, and financial performance using traditional methods and the Makassid Shariah Index (MSI) is shown in the practice of sustainable finance. The independent variable, GCG, is determined by the composite self-assessment score of each Islamic bank, value added intellectual capital (VAIC), financial performance and return on investment (ROA), net funding (NPF), and the Makassid Shariah Index (MSI) and the dependent variable, sustainable financing, is approximated by the Financial Sustainability Ratio (FSR). A study of Islamic banks in Indonesia also shows that the GCG, VAIC, ROA, NPF, and MSI variables all have a positive effect on the FSR variable, with an R-squared model value of 0.9959. variables in this study.